English negation from an interactional perspective - Cheshire, Jenny (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
This paper discusses the use of never as a strategy for expressing negation in English. I will argue that it is an important strategy, but that its importance has been overlooked because of the convention in linguistics of analysing forms in isolated sentences rather than in the conversational contexts in which they occur. This practice forces us to rely on our intuitions about the role of a given form in the structure of a language, so that we risk unwittingly describing the prescriptive norm concerning its use rather than the way in which it fits into the syntactic structure of the language.